Integrative medicine in multiple myeloma and plasma cell disorders - Onyemaechi Okolo; Betsy C. Wertheim; Ashley Larsen; Nathan W. Sweeney; Jennifer M. Ahlstrom; Krisstina Gowin (Elsevier, 2023)
Introduction: Integrative Medicine (IM) use and efficacy is poorly defined in those with plasma cell disorders (PCD). A 69-question survey on the subject was hosted on HealthTree.org for 3 months. Method: The survey included questions about complementary practice use, PHQ-2 score, quality of life, and more. Mean outcome values were compared between IM users and non-users. Proportions of supplement users and IM patients were compared between patients currently on myeloma specific treatment and patients not currently on treatment. Results: The top 10 IM modalities reported among 178 participants were aerobic exercise (83 %), nutrition (67 %), natural products (60 %), strength exercise (52 %), support groups (48 %), breathing exercises (44 %), meditation (42 %), yoga (40 %), mindfulness-based stress reduction (38 %), and massage (38 %). The survey showed most patients participated in IM modalities, though they felt uncomfortable discussing them with their oncologist. Participant characteristics were compared between groups (users and non-users) using two-sample t-tests and chi-square tests. Use of vitamin C (3.6 vs. 2.7; p = 0.01), medical marijuana (4.0 vs. 2.9; p = 0.03), support groups (3.4 vs. 2.7; p = 0.04), and massage (3.5 vs. 2.7; p = 0.03) were associated with a higher quality of life scores on MDA-SI MM. There were no other significant associations between supplement use or IM practices and the MDA-SI MM, brief fatigue inventory, or PHQ-2. Conclusion: This study provides a foundation in the understanding of IM use in PCD, but more research is needed to evaluate individual IM interventions and their efficacy.